Serological diagnosis of brucellosis in humans and pigs by Rose-Bengal Test - ΓΙΑΝΤΖΗΣ Δ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The credibility of the Rose-Bengal test as a preliminary screening test for the diagnosis of brucellosis in humanand pigs was studied. 188 samples of human and 354 of blood sera were examined with the above test in parallel with those of slow seraglutination and complement fixation tests. A closecorrelation between the results obtained by the Rose-Bengal and complement fixation tests was observed. In human the percentages of the positive sera were 48,40, 44,14% and 12,40%, while in swine were 15,53%, 14,12% and 33,39% respectively by the Rose-Bengal, complement fixation and slow sero-agglutination tests. It is concluded that the Rose-Bengal test slould be applied as a preliminary screening test for the diagnosis of Brucellosis in humans and pigs.